The fluid membrane determines mechanics of erythrocyte extracellular vesicles and is softened in hereditary spherocytosis. Issue 1 (December 2018) - Vorselen, Daan; Dommelen, Susan; Sorkin, Raya; Piontek, Melissa; Schiller, Jürgen; Döpp, Sander; Kooijmans, Sander; Oirschot, Brigitte; Versluijs, Birgitta; Bierings, Marc; Wijk, Richard; Schiffelers, Raymond; et al.
Abstract Extracellular vesicles (EVs) are widely studied regarding their role in cell-to-cell communication and disease, as well as for applications as biomarkers or drug delivery vehicles. EVs contain membrane and intraluminal proteins, affecting their structure and thereby likely their functioning. Here, we use atomic force microscopy for mechanical characterization of erythrocyte, or red blood cell (RBC), EVs from healthy individuals and from patients with hereditary spherocytosis (HS) due to ankyrin deficiency. While these EVs are packed with proteins, their response to indentation resembles that of fluid liposomes lacking proteins. The bending modulus of RBC EVs of healthy donors is ~15k b T, similar to the RBC membrane. Surprisingly, whereas RBCs become more rigid in HS, patient EVs have a significantly (~40%) lower bending modulus than donor EVs. These results shed light on the mechanism and effects of EV budding and might explain the reported increase in vesiculation of RBCs in HS patients. Red blood cell disorders are often accompanied by increased release of extracellular vesicles (EVs), but their structural and mechanical properties are not fully understood. Here, the authors show that red blood cell EVs show liposome-like mechanical features and are softened in blood disorder patients.